Saudi women’s attitudes towards e-shopping through social media - Baabdullah, Afnan bint Mohammed bin Barakat; Habib, Halima (Journal of Humanities & Social Sciences, 2018)
The purpose of this study was to recognize the attitudes of Saudi women towards electronic shopping through social media, and to explore the effect of each factor (cost, confidence, enjoyment, benefit, safety, complexity) on Saudi women in the E-shopping process. And get to know the advantages of it from Saudi women’s point of view, and to what extent they accept and adopt it, and will this type of shopping put an end to traditional shopping, and in the sake of that we used the survey method, and we applied the study through distributing (400) questionnaire - in an electronic way - among the students (female) of King Abdul-Aziz University as a simple random sample of Saudi women. The study concluded that Saudi women are familiar with this kind of shopping whereas 88% of the research sample have a positive attitudes towards it, and the results showed that Instagram is the most attractive means of E-shopping for Saudi women, and showed that what marks E-shopping from traditional shopping is the possibility to shop anytime, relief and deliver wares to the house, and the most of what obstruct the sample is identifying the texture and the quality of goods. The study indicated out that the purchasing behavior of the sample is harmonious with its cognitive, sentimental and behavioral tendencies towards e-shopping via social media. As such, the results showed that nearly half of the sample has became adoptive with this type of shopping, which indicates to the spread of this notion in Saudi society more and more, and the study showed that the most e-shopping strategies sought by Saudi women are the delivery of goods for free and the availability of pictures and videos which are illustrating the use of these goods, and also there is a high indicator between the measurement of confidence and safety for research sample in their confidence in e-shopping. The study recommended the importance of taking the obstacles of e-shopping to be considered by marketers to gain customers, and that the traditional markets need to integrate with e-shopping to maintain their customers, and take into account the credibility and quality, which is one of the most important features that must be available in electronic shopping to contribute in maintaining the old customers and gaining new customers.